2013
DOI: 10.1111/ejn.12266
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical tolerance to cocaine after initial supersensitivity in drug‐use‐prone animals

Abstract: There is great interest in outlining biological factors and behavioral characteristics that either predispose or predict vulnerability to substance use disorders. Response to an inescapable novel environment has been shown to predict a “drug-use prone” phenotype that is defined by rapid acquisition of cocaine self-administration. Here, we show that response to novelty can also predict neurochemical and behavioral effects of acute and repeated cocaine. We used cocaine self-administration under a fixed-ratio one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 44 publications
(70 reference statements)
4
31
1
Order By: Relevance
“…To examine the frequency dependence of dopamine signaling, dopamine was elicited by 5 pulse stimulations across the physiological range of dopamine neuron firing. Consistent with previous results (Ferris et al,2013a) response to novelty did not predict dopamine release magnitude in response to single pulse stimulations (Figure 1B) (r = −0.10, p = 0.68). Further, response to novelty did not predict dopamine release magnitude for any of the frequencies tested (Figure 1B; 5 Hz: r = −0.23, p = 0.35; 10 Hz: r = −0.08, p = 0.74; 20 Hz: r = −0.05, p = 0.85; 100 Hz: r = − 0.10, p = 0.69).…”
Section: 0 Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…To examine the frequency dependence of dopamine signaling, dopamine was elicited by 5 pulse stimulations across the physiological range of dopamine neuron firing. Consistent with previous results (Ferris et al,2013a) response to novelty did not predict dopamine release magnitude in response to single pulse stimulations (Figure 1B) (r = −0.10, p = 0.68). Further, response to novelty did not predict dopamine release magnitude for any of the frequencies tested (Figure 1B; 5 Hz: r = −0.23, p = 0.35; 10 Hz: r = −0.08, p = 0.74; 20 Hz: r = −0.05, p = 0.85; 100 Hz: r = − 0.10, p = 0.69).…”
Section: 0 Resultssupporting
confidence: 92%
“…In preclinical rodent models, drug abuse vulnerability can be predicted by an animal’s locomotor responsiveness to an inescapable novel environment. Indeed, animals with higher response to the novel environment (high-responder; HR) acquire drug self-administration more rapidly and at lower doses than their low-responder (LR) counterparts for many drugs of abuse, including psychostimulants such as cocaine and nicotine (Suto et al,2001; Ferris et al,2013a; Piazza et al,1989). Thus, the HR/LR model is a powerful tool for determining antecedent neurochemical characteristics that contribute to drug abuse vulnerability.…”
Section: 0 Introductionmentioning
confidence: 99%
“…Previous work has demonstrated that LgA cocaine selfadministration results in decreased cocaine potency; however, here we show no change in MPH or amphetamine potency, indicating that LgA-induced DAT changes do not affect the function of amphetamine-like compounds. This is consistent with work using a limited-intake, extended-access self-administration paradigm (5 days; 40 injections; 1.5 mg/kg per injection), which showed reduced potency of cocaine and other blockers (nomifensine, bupropion) at the DAT but no change in the potency of any releasers (amphetamine, phentermine, methamphetamine, benzypiperidine; methylenedioxymethamphetamine) or MPH (Ferris et al, 2011(Ferris et al, , 2013aCalipari et al, 2012Calipari et al, , 2014a. In addition, we show that IntA causes a sensitization of amphetamine and MPH, which is consistent with previous studies examining cocaine potency following IntA (Calipari et al, 2013c).…”
Section: Discussionsupporting
confidence: 88%
“…Despite finding no difference across groups in novel environment-induced locomotion, we did observe an increase in basal DA tone using in vivo microdialysis. While there are reports of a relationship between basal DA tone in the NAc and novel environment-induced locomotor activity (Hooks et al, 1992), others have failed to observe this relationship (Antoniou et al, 2008; Chefer et al, 2003; Ferris et al, 2013a), and thus our current finding is not without precedent. In subsequent in vitro FSCV experiments we found a reduction in evoked DA release and slower DA uptake.…”
Section: 0 Discussioncontrasting
confidence: 56%